Gender equality and digitalisation in the European Union (Vilnius, 2018)
"Digital technology has changed many things in our lives, but how is it affecting gender equality? Digitalisation has transformed the character of the labour market, changed the way we interact with our friends, shaped political participation, is impacting the future of work and also carries the risk of cyber violence. All of the above present new challenges, but also offer opportunities to address gender inequalities that affect both women and men, albeit often in different ways. The European Institute for Gender Equality (EIGE) provides some insights in this factsheet, from its work on the gender aspects of digitalisation."